At-Tabarruj dalam Perspektif Qirā’ah Mubādalah Faqihuddin Abdul Kodir - M. Aufa (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2024)
Indonesia's influence on foreign culture has had an impact, one of which is in terms of appearance or fashion. Lots of young people today are affected by inappropriate dress styles or even the impression that they are excessively ornate. In Islam, ornate is not something that is prohibited as long as it is not done excessively or what is commonly known as At-Tabarruj. At-Tabarruj is one of the things that is forbidden by Allah for Muslim women. Mufassir say that tabarruj behavior brings harm, including being able to arouse lust for men. Through this search, women are positioned as slander for men. In fact, what is seen and has happened, men also have the same potential and can become slander for women. This research is a library research that aims to interpret the meaning of At-Tabarruj in the perspective of Faqihuddin Abdul Kodir's Qira'ah Mubadalah. The results of this study explain that in Qira'ah Mubadalahh, At-Tabarruj can also be interpreted as the behavior of men who show off the beauty of their bodies so that they can arouse the lust of women and men who have tabarruj will also get rewarded with sins for doing things that prohibited by Allah. Regarding the reward for sin itself, it does not look at women or men because if he does something that is forbidden by God, he will get a reward regardless of gender.